Testing a new model combining micro-finance and farmer training to upscale the adoption of climate-smart agriculture practices by small-scale farmers in developing countries - Pamuk, Haki; Asseldonk, Marcel van; Deering, Karl; Girvetz, Evan Hartunian; Hella, Joseph; Karanja Ng'ang'a, Stanley; Masoud, Thabit; Osiemo, Jamleck; Ruben, Ruerd (2018)
This note introduces the climate-smart agriculture sustainable, productive, profitable, equitable and resilient (CSA-SuPER) research project implemented by a consortium comprising CARE International, International Center for Tropical Agriculture (CIAT), Sokoine University of Agriculture (SUA), and Wageningen University and Research (WUR).